Love Saves the Day : A History of American Dance Music Culture, 1970-1979 - Lawrence, Tim, 1967- (Book collections on Project MUSE., 2003)
Describes American dance music culture in the 1970s, profiling key events, musicians, movements, DJs, and venues that defined the era.